MYPATH: A novel mindfulness and yoga‐based peer leader intervention to prevent violence among youth experiencing homelessness. Issue 4 (8th July 2021) - Barr, Nicholas; Petering, Robin; Onasch‐Vera, Laura; Thompson, Nichole; Polsky, Ryan
Abstract: Young adults experiencing homelessness (YAEH) are at elevated risk for violence victimization and perpetration. However, there are no evidence‐based violence prevention interventions for homeless populations. This study is an evaluation of a novel mindfulness‐based peer‐leader intervention designed to reduce violence and improve mindfulness in YAEH. A social network of YAEH receiving services at a drop‐in agency was recruited in Summer 2018 ( n  = 106) and peer‐leaders identified at baseline ( n  = 12). Peer leaders were trained in mindfulness and yoga skills during a 1‐day intensive workshop and seven 1‐h weekly follow‐up workshops and encouraged to share their knowledge with in‐network peers. Postintervention data were collected 2 and 3 months after baseline. Two one‐way repeated‐measures analyses of variance (ANOVAs) tested differences in means for mindfulness and fighting. ANOVA models showed significant increases in group mean mindfulness F (2, 110) = 3.42, p  < 0.05 and significant decreases in group mean violent behavior F (2, 112) = 5.23, p  < 0.01 at the network level. Findings indicate a network‐based, peer‐leader model can be effective for influencing complex, socially conditioned attitudes and behaviors among YAEH. Additional advantages of the peer‐leader model include relatively few direct‐service person‐hours required from providers and convenience to participants able practice skills in their relevant social contexts. HIGHLIGHTS: This article is evaluates the effectiveness of MYPATH, a novel mindfulness and yoga based peer‐leader intervention to reduce violence in young adults experiencing homelessness. There are no existing evidence based interventions to reduce violence in this population, but violence is a barrier to exiting homelessness and impedes access to services and resources. Results of the present study show that MYPATH is associated with increased mindfulness and decreased violence behaviors in the study sample from baseline to posttest and follow‐up MYPATH presents a template for decentralized, peer‐leader driven, social network interventions which may be effective for engaging difficult to reach but well‐networked populations like the young adults experiencing homelessness in this sample.